2015
DOI: 10.2215/cjn.07490714
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning

Abstract: Background and objectives More than 90,000 patients with ESRD die annually in the United States, yet advance care planning (ACP) is underutilized. Understanding patients' and families' diverse needs can strengthen systematic efforts to improve ACP.Design, setting, participants, & measurements In-depth interviews were conducted with a purposive sample of patients and family/friends from dialysis units at two study sites. Applying grounded theory, interviews were audiotaped, professionally transcribed, and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 46 publications
5
102
0
3
Order By: Relevance
“…A randomized controlled trial in an elderly general medical population has shown that advance care planning improves end-of-life care, patient and family satisfaction and reduces stress, anxiety, and depression in surviving relatives (16). A similar study has yet to be done BOX 2 -Timing of end-of-life discussions 1 in the dialysis population; yet patient interviews suggest that most participants felt that advance care planning is important and should start early in the disease course, but that it rarely takes place at all (17).…”
Section: Advance Care Planningmentioning
confidence: 99%
“…A randomized controlled trial in an elderly general medical population has shown that advance care planning improves end-of-life care, patient and family satisfaction and reduces stress, anxiety, and depression in surviving relatives (16). A similar study has yet to be done BOX 2 -Timing of end-of-life discussions 1 in the dialysis population; yet patient interviews suggest that most participants felt that advance care planning is important and should start early in the disease course, but that it rarely takes place at all (17).…”
Section: Advance Care Planningmentioning
confidence: 99%
“…(25) This sentiment is echoed in more recent qualitative studies describing the experiences and perspectives of caregivers and family members of patients with advanced kidney disease as they pertain to specific treatments (e.g., hemodialysis, supportive care) (26)(27)(28)(29)(30)(31), advance care planning (ACP) (32), and end-of-life care (33)(34)(35). To our knowledge, no prior studies have attempted to characterize more broadly the experiences of family members and friends of patients with advanced kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although nephrologists are integral members of the team in the advance care planning process, if they have done an effective job, advance care planning topics would have been introduced and discussed in most cases during the course of CKD management, long before dialysis was initiated. As again demonstrated by the participants in the study by Goff et al, dialysis patients believe that advance care planning should be started early in the course of CKD and revisited at intervals (6). Interestingly, Goff et al report that several of their patients had engaged in advance care planning discussions with their primary care physicians.…”
mentioning
confidence: 96%
“…Goff et al suggest that patient experience with death or severe illness in a family member may facilitate advance care planning (6). A study of 43 in-center hemodialysis patients in the 1990s failed to show that experience with potentially life-threatening illness in the patient or a family member influenced completion of advance directives, a surrogate end point of successful advance care planning (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation